Oncostatin M-driven macrophage-fibroblast circuits as a drug target in autoimmune arthritis - Nam Cong-Nhat Huynh; Rui Ling; Masatsugu Komagamine; Tianshu Shi; Masayuki Tsukasaki; Kotaro Matsuda; Kazuo Okamoto; Tatsuo Asano; Ryunosuke Muro; Warunee Pluemsakunthai; George Kollias; Yuko Kaneko; et al. (BMC, 2024)
Abstract Background Recent single-cell RNA sequencing (scRNA-seq) analysis revealed the functional heterogeneity and pathogenic cell subsets in immune cells, synovial fibroblasts and bone cells in rheumatoid arthritis (RA). JAK inhibitors which ameliorate joint inflammation and bone destruction in RA, suppress the activation of various types of cells in vitro. However, the key cellular and molecular mechanisms underlying the potent clinical effects of JAK inhibitors on RA remain to be determined. Our aim is to identify a therapeutic target for JAK inhibitors in vivo. Methods We performed scRNA-seq analysis of the synovium of collagen-induced arthritis (CIA) mice treated with or without a JAK inhibitor, followed by a computational analysis to identify the drug target cells and signaling pathways. We utilized integrated human RA scRNA-seq datasets and genetically modified mice administered with the JAK inhibitor for the confirmation of our findings. Results scRNA-seq analysis revealed that oncostatin M (OSM) driven macrophage-fibroblast interaction is highly activated under arthritic conditions. OSM derived from macrophages, acts on OSM receptor (OSMR)-expressing synovial fibroblasts, activating both inflammatory and tissue-destructive subsets. Inflammatory synovial fibroblasts stimulate macrophages, mainly through IL-6, to exacerbate inflammation. Tissue-destructive synovial fibroblasts promote osteoclast differentiation by producing RANKL to accelerate bone destruction. scRNA-seq analysis also revealed that OSM-signaling in synovial fibroblasts is the main signaling pathway targeted by JAK inhibitors in vivo. Mice specifically lacking OSMR in synovial fibroblasts (Osmr ∆Fibro) displayed ameliorated inflammation and joint destruction in arthritis. The JAK inhibitor was effective on the arthritis of the control mice while it had no effect on the arthritis of Osmr ∆Fibro mice. Conclusions OSM functions as one of the key cytokines mediating pathogenic macrophage-fibroblast interaction. OSM-signaling in synovial fibroblasts is one of the main signaling pathways targeted by JAK inhibitors in vivo. The critical role of fibroblast-OSM signaling in autoimmune arthritis was shown by a combination of mice specifically deficient for OSMR in synovial fibroblasts and administration of the JAK inhibitor. Thus, the OSM-driven synovial macrophage-fibroblast circuit is proven to be a key driver of autoimmune arthritis, serving as a crucial drug target in vivo.